Pengaruh Digital WOM Dan Personal Branding Influencer Tasya Farasya Terhadap Persepsi Produk Kosmetik Yang Berdampak Pada Keputusan Pembelian - Laurency Marcelia; Lizna Rizqyana; Nesya Allaya Hermansyah (Jurnal Strategi Bisnis Teknologi, 2024)
This study explores the influence of digital WOM (Word of Mouth) and Tasya Farasya's personal branding on cosmetic product purchasing decisions. Using the online survey method, data was collected from respondents who are social media users. The results of the regression analysis show that there is a positive relationship between digital WOM and Tasya Farasya's personal branding and decisions to purchase cosmetic products. The managerial implications of these findings help cosmetic brands in developing effective marketing strategies through the use of digital WOM and collaboration with leading personal brands such as Tasya Farasya.